Case Study of Deep Breath Relaxation Intervention to Reduce Chronic Pain Scale in Post-Brachial Tumor Surgery Patients - Nurhidayat, Rizki; Fitriani, Ade; Hidayat, Nur (Yayasan Inspirasi El Burhani, 2023)
Objective: This case study was conducted to describe deep breathing relaxation. intervention in reducing the pain scale in postoperative clients of brachial tumors. Method: This exploration uses an expressive contextual investigation plan with a nursing care approach. with participants based on inclusion and exclusion criteria. Gather information through interviews, perceptions, actual assessments, and documentation evidence-based practice focused on nursing interventions. The research was conducted at the BLUD RSU Banjar City on 27-31 May 2022. The participants in this study were Mr. W's client, 61 years old, male, complaining of postoperative pain. The process of assessment and diagnosis is focused on the main problem. Objective and subjective data become a reference for periodic evaluations of nursing implementation. Results: The results obtained from the nursing process which consisted of assessment, nursing diagnoses, interventions, implementation and evaluation for 4 days starting May 27-31 2022 the authors took one of the nursing diagnoses, namely pain, therefore the intervention carried out was deep breathing. Relaxation techniques to reduce pain, pain scale in postoperative brachial tumor patients with the result of reducing the pain scale from a pain scale of 5 to 2 pain scale. Conclusion: Deep breathing relaxation intervention after the researcher carried out nursing care for Mr. W Pain Diagnosis there is a significant decrease in pain scale. To maintain the conditions that have been achieved, it is hoped that the role of Mr. W's family is to be able to follow the treatment thoroughly for the client's recovery and as an effort to prevent complications of diseases associated with brachial tumors.